Comparison of micafungin and voriconazole as empirical antifungal therapies in febrile neutropenic patients with hematological disorders: a randomized controlled trial. (26th August 2015) - Oyake, Tatsuo; Kowata, Shugo; Murai, Kazunori; Ito, Shigeki; Akagi, Tomoaki; Kubo, Kohmei; Sawada, Kenichi; Ishida, Yoji
Abstract: Objectives: In cases of hematological malignancy, patients with persistent fever and neutropenia receive antifungal empirical therapy to prevent and treat invasive fungal infections. The clinical efficacy and safety of micafungin and voriconazole were compared. Methods: In this randomized, cooperative group, open‐label trial, we assessed and compared the efficacy and safety of micafungin and voriconazole as an empirical antifungal therapy in febrile neutropenic patients with hematological malignancy. Patients were classified according to invasive fungal infection risk. Results: There were no significant differences in clinical efficacy between the two treatments, evaluated based on (i) successful treatment of baseline fungal infection (no evaluation), (ii) absence of breakthrough fungal infection ( P  = 0.106), (iii) survival for ≥7 days after study completion ( P  = 0.335), (iv) premature study discontinuation due to poor efficacy ( P  = 0.424), and (v) resolution of fever during neutropenia ( P  = 0.756). Discontinuation due to drug‐related adverse events (grades 3‐4) occurred less frequently in the micafungin group ( P  = 0.005). Conclusions: The clinical efficacy did not differ between micafungin and voriconazole. Micafungin was generally better tolerated than voriconazole when given as an empirical antifungal therapy in patients with persistent fever and neutropenia.